Moving landscapes of Nordic basic education: approaching shifting international influences through the narratives of educational experts. Issue 6 (17th August 2020) - Hansen, Petteri; Wallenius, Tommi; Juvonen, Sara; Varjo, Janne
ABSTRACT: Throughout history educational leaders have looked to other countries and have attempted to learn by borrowing useful examples to implement in their own educational systems. As recent comparative policy research shows, processes of policy lending and borrowing have their own socio-historically defined dynamics. In this paper, the authors approach the use of reference countries through narratives of educational experts in Finland, Norway and Sweden. By comparing how international influences are used in stories about basic education, this research constructs a core narrative of a moving Nordic landscape. This landscape indicates both recognised and acknowledged policy borrowing relations in the past, as well as a changing orientation to preferred and avoided reference countries in the present. While new country-specific performance indicators such as PISA have widened the landscape of reference countries at an official level, culturally mediated images seem to redefine how reference countries are observed in everyday semantics.